Polycondensation History and New Results - Kricheldorf, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book reports on origin and history of polycondensation chemistry beginning in the first half of the 19th century. Furthermore, history and inventors of the most important polycondensates, such as Nylons, PET or polycarbonates, are described. The classical theory of step-growth polymerizations is discussed in the light of the latest experimental and theoretical results. Particular emphasis is laid on the role of cyclization reactions. Special categories of polycondensation processes are discussed in more detail: syntheses of hyperbranched and multicyclic polymers, non-stoichiometric polycondensations, interfacial polycondensations, solid state polycondensations, condensative chain polymerizations etc.
Experiments before World War I -- W.H. Carothers - Life and Work -- P.J. Flory and the Theory of Step-Growth Polymerization -- W. Stockmayer and the Role of Equilibration -- Important Polycondensates -- The Role of Cyclization and a new Theory of Step-Growth Polymerization -- Non-Stoichiometric Polycondensations -- Ring-Opening Polycondensation -- Multibranched Polymers by a2 + bn Polycondensations -- Hyperbranched Polymers by abn Polycondensations -- Multicyclic Polymers -- Polycondensations via Electrostatic Interactions -- Solid State Polycondensations -- Combined Ring-Opening Polymerization and Polycondensation -- Condensative Chain Polymerization.
Keywords: Chemistry; Chemistry, Organic; Polymers; Chemistry; Polymer Sciences; Organic Chemistry